2010
DOI: 10.1159/000319467
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in Human Term Placenta: Morphology and Phenotype

Abstract: In the last few years, a new cell type – interstitial Cajal-like cell (ICLC) – has been described in digestive and extra-digestive organs. The name has recently been changed to telocytes (TC) and their typical thin, long processes have been named telopodes (TP). To support the hypothesis that TC may also be present in human placenta and add to the information already available, we provide evidence on the ultrastructure, immunophenotype, distribution, and interactions with the surrounding stromal cells of TC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
185
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 91 publications
12
185
0
1
Order By: Relevance
“…They were not searched then for the CD34 expression. It was documented that, in human chorial villi, some TCs are CD34-positive, some are c-kit-positive [15,41]. Here a CD34-positive but c-kit-negative phenotype was found.…”
Section: Discussionmentioning
confidence: 98%
“…They were not searched then for the CD34 expression. It was documented that, in human chorial villi, some TCs are CD34-positive, some are c-kit-positive [15,41]. Here a CD34-positive but c-kit-negative phenotype was found.…”
Section: Discussionmentioning
confidence: 98%
“…F, fibroblast; N, nucleus; Nf, nerve fiber; Pd, podomer; Pm, podom; SMC, smooth muscle cell; Tc, telocyte; Tp, telopode. reporting the presence of TCs in other organs, including the epicardium (20), myocardium (21), endocardium (26), placenta (27) and skin (28). The role of TCs is unclear; however, based on the available data, numerous potential and relevant roles have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Manole et al (36) demonstrated that TCs are involved in neo-angiogenesis in experimental acute myocardial infarction. TCs may further be involved in tissue regeneration and reparation (28,18); it is suggested that TCs are involved in angiogenesis, as it has been demonstrated that TCs express CD34 and VEGF (27).…”
Section: Discussionmentioning
confidence: 99%
“…They are connected with each other through gap junctions or desmosomes (45,47,49). TCs accompanying capillaries frequently establish heterocellular contacts with pericytes and endothelial cells.…”
Section: Intercellular Junctionsmentioning
confidence: 99%
“…Such phenomenon was observed in human term placenta, where TCs form a network around myofi broblasts and VSMCs. This regulatory mechanism may include NO signalisation, since some of the network-forming TCs expressed iNOS (49).…”
Section: Physiological Role Of Vascular Tcsmentioning
confidence: 99%